Chitosan biguanide induced mitochondrial inhibition to amplify the efficacy of oxygen-sensitive tumor therapies. (1st November 2022) - Zhou, Zaigang; Zheng, Chunjuan; Liu, Yu; Luo, Wenjuan; Deng, Hui; Shen, Jianliang
Abstract: At present, the tumor's poor oxygen perfusion and limited tumor drug permeation are the major bottlenecks that limit the therapeutic effectiveness of the oxygen-sensitive antitumor therapies, like doxorubicin (Dox)-mediated chemotherapy and photodynamic therapy (PDT). To our best knowledge, the abnormal tumor mitochondria oxidative phosphorylation (OXPHOS) was the vital cause of such phenomenon, which induced the hypoxia tumor microenvironment and enhanced drug efflux from tumor cells via enhanced multidrug resistance protein 1 (MDR-1) expression. In this study, it was newly revealed that biguanide-modified chitosan (Bi-Ch) possessed ideal mitochondria depression capacity, leading to the following decreased dosage needed to disrupt mitochondrial function to reverse tumor hypoxia and depress MDR-1 expression. By doing this, Bi-Ch effectively enhanced Dox accumulation in tumor cells and amplified its cytotoxicity owing to the amplified ROS generation by Dox. Therefore, Bi-Ch could be used to improve the efficacy of oxygen-sensitive tumor therapies in vitro . Graphical abstract: Unlabelled Image